Practicality and Effectiveness of Augmented Reality Integrated Learning Media on the Material of Atomic Theory Development on the Learning Outcomes of Phase E SMA/MA Students - Septiani, Ulfa; Guspatni, Guspatni; Yerimadesi, Yerimadesi; Yusmaita, Eka (FKIP - Universitas Riau, 2025)
Augmented Reality integrated media has the ability to display concept visualizations. Augmented Reality integrated media on the material of atomic theory development has been developed by previous researchers. This study aims to determine the level of practicality of Augmented Reality integrated media on the material of atomic theory development in learning and its effectiveness on learning outcomes. The type of research used is pre-experimental with a research design, namely One-group Pretest-Posttest Design. The sample class is X E.1 SMA Negeri 1 Sabak Auh. The instrument used in the practicality test is a questionnaire while the effectiveness test uses a cognitive knowledge test instrument in the form of multiple choices. The results of the study obtained a practicality value of 0.92 while the effectiveness test showed an average N-gain value of 0.72 in the high category. Hypothesis testing using the Wilcoxon match pairs test assisted by SPSS at a significance level of 0.05 obtained an Asymp. Sig. (2-tailed) value of <0.000 with the hypothesis decision accepted. So it can be stated that the integrated Augmented Reality learning media on the material on the development of atomic theory has proven effective in significantly improving student learning outcomes.